Time to Completion of Two-Step Screening for Gestational Diabetes and Adverse Outcomes - Nazeer, Sarah A.; Chen, Han-Yang; Cornthwaite, Joycelyn A.; Sadek, Sandra; Ghorayeb, Tala; Daye, Nahla; Chauhan, Suneet P.; Sibai, Baha; Bartal, Michal F. (American Journal of Perinatology, 2023)
Objective This study aimed to ascertain whether the length of time to complete the gestational diabetes mellitus (GDM) screening was associated with adverse neonatal outcomes.Study Design This was a retrospective cohort study of singleton, nonanomalous individuals who were screened for GDM at ≥24 weeks' gestation at an academic hospital system. We compared outcomes among people who were diagnosed with GDM and completed the 3-hour glucose tolerance test (GTT) ≤14 second versus >14 days from the 1-hour glucose challenge test (GCT). The primary outcome was a composite adverse neonatal outcome of the following: large for gestational age, shoulder dystocia, birth injury, respiratory distress, hypoglycemia, or fetal/neonatal death. The secondary outcomes included several individual neonatal and maternal morbidities. Multivariable Poisson's regression models were used to evaluate the association. Adjusted relative risk (aRR) and 95% confidence intervals (CI) were calculated.Results Among the 313 individuals who completed the two-step screening for GDM and had an 1-hour GCT ≥ 135 mg/dL; of them, 171 (54.6%) completed the 3-hour GTT ≤14 days, 142 (45.4%) completed the 3-hour GTT > 14 days. Overall rate of the primary outcome was 44.1%. After multivariable adjustment, the risk of the primary outcome was similar between people who completed the two-step method in ≤14 versus >14 days (aRR = 1.11, 95% CI = 0.81–1.52). There was no significant difference in all secondary adverse outcomes between the two groups. Subgroup analyses, limited to people diagnosed with GDM (N = 89, 23.4%), also found similar results as the full analyses.Conclusion Among individuals who completed the two-step screening for GDM, completion of the 3-hour GTT within ≤14 versus ≥ 14 days was not associated with an increase rate of the adverse outcomes.Key Points
Keywords: gestational diabetes; screening; glucose tolerance test; large for gestational age